2020
DOI: 10.1111/dth.13663
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up effect of omalizumab in chronic spontaneous urticaria and its association with serum C‐reactive protein levels

Abstract: This study aims to determine the efficacy of omalizumab, a humanized monoclonal anti‐immunoglobulin E antibody, in patients with chronic spontaneous urticaria (CSU) refractory to conventional therapy, together with the evaluation of serum CRP levels. All the patients with a diagnosis of CSU who were continuously treated with omalizumab (300 mg/mo) for at least 3 months between June 2016 and July 2019 were included in this study. Urticaria activity score (UAS‐7) was used for assessment of disease activity. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Additionally, it was seen that CRP levels remained lower than baseline levels at 12 months follow-up. In another study, it was seen that CRP levels significantly correlated with disease activity (UAS7) at baseline and after treatment with omalizumab, indicating anti-inflammatory effects of omalizumab [24].…”
Section: C-reactive Proteinmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, it was seen that CRP levels remained lower than baseline levels at 12 months follow-up. In another study, it was seen that CRP levels significantly correlated with disease activity (UAS7) at baseline and after treatment with omalizumab, indicating anti-inflammatory effects of omalizumab [24].…”
Section: C-reactive Proteinmentioning
confidence: 93%
“…CRP: While CRP correlates with disease activity [23,24], it is not a useful predictor for response to omalizumab treatment. However, it has been suggested that CRP is more useful in differential diagnosis, where a high CRP level that does not decrease during treatment could be an indicator of auto-inflammatory syndrome [22].…”
Section: Basic Diagnostic Workupmentioning
confidence: 99%
“…Yaldiz and Asil [97] found that CRP levels and HDL levels are negatively correlated, so CU may increase the risk of atherosclerosis [97]. For CSU patients with poor effect of antihistamines, their plasma CRP levels are significantly increased [98], for patients treated with omalizumab, and CRP levels significantly decreased after 12 weeks of treatment and are closely associated to UASs [99]. Therefore, CRP can serve as a marker for individualized treatment of patients: omalizumab can be chosen, instead of antihistamines, and also can be used evaluate CU patients' risk of developing atherosclerosis.…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…Dreyfus thought that long‐term OMZ therapy may be required to decrease HHV‐6 titers 10 . Interestingly, OMZ has been used safely for CSU continuously for up to 25 months, according to a recent study from Turkey 11 . An antiviral potential of OMZ may stand behind its mechanism of action in treatment of respiratory viral infections, including SARS‐CoV‐2, and secondary activated endogenous viruses, such as HHV‐6, that are involved in the pathogenesis of CSU or chronic viral urticaria 7,9,10 .…”
mentioning
confidence: 99%